The knowledge, practices and perceptions in drug management among the nursing staffs and its relationship to medication error at Hospital Sultan Abdul Halim, Sungai Petani - Ahmad Mayzian, Nur Adrin; Zakuwan, Nurul Shafika (2018)
Improper drug management and medication errors are very much highlighted and being a focus topic especially in nursing study. In daily practices, nurses are responsible with administration of drugs to patients therefore they are highly exposed to risks of drug mix-ups error. Proper administration of medication is nurse responsibility, so it is important for them to counteract errors and practicing the right way of drug management. This study is important to ensure that nurses manage the medication properly besides to prevent medication errors and improper drug management. This study is to evaluate the level of knowledge in drug management among the nursing staff at Hospital Sultan Abdul Halim (HSAH), to compare the knowledge level in drug management between gender of nursing staffs at HSAH, to compare the knowledge score in drug management between working experience and ward among the nursing staffs at HSAH and lastly to understand the practices and perceptions in drug management among nursing staff at HSAH. In this study, a form of questionnaire is used to determine the level of knowledge, practice and perceptions in drug management among nursing staffs at HSAH and its relationship to medication error. Next, the data collected was analyzed by using SPSS version 23. In short, our scope of study is HSAH nursing staff which age are about 20-36 years old and above with total up around 80 nurses as our respondents to finish this research study. Findings of the study indicated that most of the respondents obtained a moderate score (3-4 marks per 6 marks) for knowledge in drug management. Knowledge score of drug management is higher in female respondents compare to male respondents. Also, the result indicated that knowledge in drug management was influenced by working experience but there was no effect of ward. Moreover, results showed that most of the nursing staff did not follow right procedure and practices in drug management. Findings from this study suggested that medication errors and improper drug management are still quite rampant in HSAH, thus nurses should play an important roles to reduce this mistakes. Hence, nursing staffs should be very well exposed on drug management to guarantee that they are well equipped with enough knowledge and skills for safe practice.